Chemical composition and anti-aging effects of standardized herbal chicken essence on D-galactose- induced senescent mice - Wu, Shu-Jing; Tung, Yi-Jou; Yen, Ming-Hong; Ng, Lean-Teik (Frontiers in Nutrition, 2022)
This study aimed to examine the chemical and anti-aging properties of chicken essence (CE) prepared with Sesamum indicum, Angelica acutiloba, and Zingiber officinale (HCE). HCE was analyzed for nutritional and phytochemical composition, and its anti-aging effects were investigated on the D-galactose (Gal)-induced aging mice. Results showed that HCE possessed significantly higher calories and contents of valine and total phenols than CE; it also contained significant amounts of ferulic acid, sesamin, and sesamolin. HCE significantly decreased MDA and NO levels in serum and liver, and increased liver GSH levels in the D-Gal-induced mice. HCE greatly enhanced SOD and CAT activities in serum and liver, and liver GPx activity, as well as up-regulating SIRT1 expression and down-regulating TNF-α, IL-1β, IL-6, iNOS, Cox-2, and MCP-1 expression in liver tissues. This study demonstrates that HCE was effective in suppressing the aging process through enhancing antioxidant and anti-inflammatory activities, and modulating the aging-related gene expression.